STRATEGI PEMASARAN PEDAGANG PASAR TRADISIONAL DALAM PERSPEKTIF EKONOMI ISLAM - Arwani, Arwani (LPPM IAI Pangeran Dharma Kusuma Segeran Indramayu, 2022)
Business in the world of trade is one of the most important things in human life. Every human being needs property and wealth to fulfill their needs. The market is a center of economic activity that encourages and facilitates economic activities for society. The diversity of traders and several underlying factors, both internal and external, make the trading behavior and strategies of traders different. starting from promoting goods, discount prices, bonuses, discounts or selling goods at cheaper prices. Karangampel Indramayu Traditional Market, is one of the markets in the eastern part of Indramayu City. It is a place of trade and service sector activities. This is proven by the existence of a market that is still popular with consumers and middlemen from several regions. strategies carried out by traders on several types of merchandise. Such as giving discounts and bonuses. So it is feared that this could lead to strategy deviations in trading. Such as elements of fraud (gharar), dishonesty, are things that are prohibited in Islamic law. The research method that the author uses is qualitative research with field research. In this research consists of data sources, namely primary data sources (data obtained directly from original sources (not through intermediaries) and secondary data sources (research data sources obtained by researchers indirectly through intermediaries (obtained and recorded by other parties), while for data collection techniques using interviews, documentation and observation. The final step in the research method is data analysis. The research results: show that the marketing strategy carried out by traditional market traders is a mix of marketing (marketing mix) which consists of product, price and promotion. And a strategy that is not appropriate is mixing goods of good quality with those of ordinary quality without being honest about explaining the matter or condition of the merchandise.